A Systematic Review of Determinants Influencing Drug Availability in Community Health Centers in Indonesia - Raymanus, Melani Angela Indrayani; Satibi, Satibi; Puspandari, Diah Ayu (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2025)
Background: Drug availability in community health centers is a critical component in delivering quality health services to the community.drugSeveral factors  influence drug availability, including the procurement process, stock management, and geographic distribution of health facilities.Objectives: This study aims to  to review the factors that influence  drug availability in Indonesian community health centers.Methods: This study  conducted  a systematic review of  published articles in English that reported on factors influencing drug availability published during year 2016 to 2024. Relevant studies were located through an extensive search from four database (Scopus, PubMed, GARUDA, and Google Scholar). These keywords provide the necessary information. The quality of the included studies was assessed using Joanna Briggs Institute JBI  critical appraisal tools, including extensions tailored to various systematic review research designs.Results: Initially, 996 identified articles were screened by titles, abstracts, and full texts based on predefined inclusion and exclusion criteria, resulting in 25 eligible studies. This review identified twenty-fivestudies that focused on various regions in Indonesia, from large urban areas to remote areas. The main factors influencing drug availability include inadequacy planning and procurement processes, lack of knowledge, lack of pharmaceutical personnel, change in disease patterns and prescription patterns, the suboptimal use of the management information system and limited availability of drug at Health Office.Conclusion: Suboptimal drug availability continues to occur frequently across various regions in Indonesia. Key improvement efforts should focus on increasing knowledge of drug management, the number of pharmacies, and providing a sufficient budget for the procurement of drug.. Future research should prioritize  areas outside the main islands to develop targeted solutions to address local challenges.